The effect of hand position on chest compression quality during CPR in young children: Findings from the Videography in Pediatric Resuscitation (VIPER) collaborative. (April 2023) - O'Connell, Karen J.; Sandler, Alexis; Dutta, Anuj; Ahmed, Ramzy; Neubrand, Tara; Myers, Sage; Kerrey, Benjamin; Donoghue, Aaron
Abstract: Objective: To determine the effect of hand position on chest compression (CC) quality during CPR in young children. Methods: Prospective observational exploratory study. Patients < 8 years receiving CC for > 2 minutes were enrolled. Data was collected from video review and CC monitor device and analyzed in 'CC segments' (periods of CC by individual providers). Four techniques were compared: two thumbs (2 T), hands encircling the chest; two fingers (2F) on the sternum; one hand on sternum (1H); two hands on sternum (2H). Univariate analysis of CC rate and depth between hand positions was performed through nonparametric testing, stratified by age category. Results: 47 patients received 824 minutes of CC. Among 270 CC segments in infants < 1 yo, 2 T was used in 27%; 2F 3%; 1H 18%; 2H 26%. Among 189 CC segments in children aged 1 to 8 yo, 1H was used in 26%; 2H 74%. Across all segments, median CC rate was 117 cpm (IQR 110–125). Median depth was 2.92 cm (IQR 2.44 – 4.04) in infants < 1 yo, 3.56 cm (IQR 2.92 – 4.14) in children 1 to 8 yo. 1H achieved greater depth than 2 T in infants (p < 0.01), and 2H achieved greater depth than 1H in children > 1 (p < 0.001). Conclusions: In infants, 1H resulted in greater CC depth than 2 T. In children 1 to 8 yo, 2H resulted in greater depth than 1H.. These data suggest that different hand position during CPR in young children from what is currently recommended may result in better CPR quality.